Influência da redução do grão cristalino e fatores de desordem química na transição de fase de primeira ordem da liga tipo Heusler Ni2Mn1,44Sn0,56 - Alves, André Luíz (2011)
In this work, we investigated the influence of the grain refinement and the effect of chemical disorder induced by high energy milling on the martensitic transformation of the Ni2Mn1,44Sn0,56 Heuler-type alloy with and without Fe doping in the different crystallographic sites of the L21-type structure. We used X-ray diffraction to estimate the grain size as a function of milling time and DC magnetization to study the magnetic properties and the martensitic transformation of this alloy. We determined that the increasing of milling time induces a grain size reduction, enhancing substantially the grain boundary regions, which have high chemical and topological disorder degrees and favoring magnetically frustrated spin configurations. We applied Mössbauer spectroscopy of 119Sn and of 57Fe to characterize the different magnetic fractions and to follow locally the magnetism of this alloy. The main results caused by the disorders induced by milling are the increasing of the Exchange Bias Field and a significant reduction of the magnetocaloric properties of the Ni2Mn1,44Sn0,56 Heusler-type alloy when the milling time is increased. The enhancement of the Exchange Bias Field, we have explained based on the increasing of the fractions of the antiferromagnetic and/or frustrated spin of the grain boundary regions relatively to the ferromagnetic grain core fraction when the milling time is increased. On the other hand, we conclude that the decrease of the magnetic entropy change (magnetocaloric effect) is due to the magnetization changes during the martensitic phase transformation, which depends on the fractions of the grain cores. Therefore, this reductions is correlated to the increase of the grain boundary regions, which have low magnetization and has not martensitic phase transformation. From the Fe doping effect on different crystallographic sites of the L21- B2 - type structure of the Ni2Mn1,44Sn0,56 Heusler-type alloy, we demonstrated X that the distint shapes and features/properties of the magnetization curves are due to the different fractions of Fe ferromagnetically coupled with Mn at room temperature. We also shown that a heat treatment on the milled alloy restores the L21 – B2 -type structure and improves the mains magnetic properties related to the structural phase transformation called as martensitic